Evaluation of a credit-bearing online administered happiness course on undergraduates’ mental well-being during the COVID-19 pandemic - Hobbs, Catherine; Jelbert, Sarah; Santos, Laurie R.; Hood, Bruce (PLOS ONE, 2022)
Psychoeducational courses focused on positive psychology interventions have been shown to benefit student well-being. However, since the onset of the COVID-19 pandemic and accompanying social restrictions, many educators have had to deliver their courses online. Given that online teaching presents a very different university experience for students, do psychoeducational courses provide similar well-being benefits in an online format? In this pre-registered study (https://osf.io/3f89m), we demonstrate that despite the challenges of remote learning, first year university students (N = 166) taking an online “Science of Happiness” course during the first term experienced positive benefits to mental well-being in comparison to a wait-list control group (N = 198) registered to take the course in the second term. Specifically, university students currently taking the course maintained their mental well-being over the semester relative to the wait-list control who showed a significant decline in well-being and increase in anxiety during the same period. Our findings suggest that the online-administered “Science of Happiness” course delivered during the COVID-19 pandemic was associated with a protective effect on mental well-being. We also observed that engagement with the course was high, though there was no evidence that this factor mediated the positive effects we observed. However, we did find evidence that prior interest in increasing well-being influenced the effects of the course; participants with lower well-being interest showed less of a benefit. Our results suggest that online psychoeducational courses might provide a relatively cheap, flexible, and efficient means of providing support as part of an integrated approach to student mental well-being.